Antagonistic and Synergistic Activation of Cardiovascular Vagal and Sympathetic Motor Outflows in Trigeminal Reflexes - Buchholz, Bruno; Kelly, Jazmín; Bernatene, Eduardo A.; Méndez Diodati, Nahuel; Gelpi, Ricardo J. (Frontiers in Neurology, 2017)
The trigeminal nerve and heart are strongly related through somato-autonomic nervous reflexes that induce rapid changes in cardiovascular function. Several trigeminal reflexes have been described, but the diving and trigeminocardiac reflexes are the most studied. The heart is a target organ dually innervated by the sympathetic and parasympathetic systems. Thus, how cardiac function is regulated during the trigeminal reflexes is the result of the combination of an increased parasympathetic response and increased, decreased or unaltered sympathetic activity. Various hemodynamic changes occur as a consequence of these alterations in autonomic tone. Often in the oxygen-conserving physiological reflexes such as the diving reflex, sympathetic/parasympathetic co-activation reduces the heart rate and either maintains or increases blood pressure. Conversely, in the trigeminocardiac reflex, bradycardia and hypotension due to parasympathetic activation and sympathetic inactivation tend to be observed. These sudden cardiac innervation disturbances may promote the generation of arrhythmias or myocardial ischemia during surgeries in the trigeminal territory. However, the function and mechanisms involved in the trigeminal reflexes remain to be fully elucidated. The current review provides a brief update and analysis of the features of these reflexes, with special focus on how the autonomic nervous system interacts with cardiovascular function.